Infertility-related stress and quality of life in women experiencing concurrent reproductive trauma. (3rd April 2022) - Swift, Alison; Reis, Pamela; Swanson, Melvin
Abstract: Purpose: To compare differences in infertility-related stress and quality of life (QOL) among women with infertility and concurrent reproductive trauma, defined as pregnancy loss during the infertility experience. Materials and Methods: We used a descriptive, cross-sectional study design to recruit 205 women who underwent infertility treatments from infertility-related Facebook support groups and pages. Participants completed the Copenhagen Multi-center Psychosocial Infertility Fertility Problem Stress Scale, the Fertility Quality of Life tool, and a supplemental infertility demographic form. Statistical analyses included descriptive statistics, Pearson correlations, multivariate analysis of variance (MANOVA), univariate ANOVA, and eta squared. Statistical significance was evaluated using a Bonferroni adjusted alpha = .05/7 = .007. Results: Participants with concurrent reproductive trauma had significantly higher social stress ( p < .001), and significantly lower emotional QOL ( p = .003) than women with infertility alone. Although not statistically significant, participants with concurrent reproductive trauma reported higher personal and marital stress scores and lower mind/body, relational, and social QOL scores than women with infertility alone. Conclusions: Women with concurrent reproductive trauma may need psychological support to combat the emotional distress of pregnancy loss during infertility treatment.